Brainstem evoked auditory potentials in tinnitus: A best-evidence synthesis and meta-analysis - Jacxsens, Laura; De Pauw, Joke; Cardon, Emilie; van der Wal, Annemarie; Jacquemin, Laure; Gilles, Annick; Michiels, Sarah; Van Rompaey, Vincent; Lammers, Marc J. W.; De Hertogh, Willem (Frontiers in Neurology, 2022)
Introduction Accumulating evidence suggests a role of the brainstem in tinnitus generation and modulation. Several studies in chronic tinnitus patients have reported latency and amplitude changes of the different peaks of the auditory brainstem response, possibly reflecting neural changes or altered activity. The aim of the systematic review was to assess if alterations within the brainstem of chronic tinnitus patients are reflected in short- and middle-latency auditory evoked potentials (AEPs). Methods A systematic review was performed and reported according to the PRISMA guidelines. Studies evaluating short- and middle-latency AEPs in tinnitus patients and controls were included. Two independent reviewers conducted the study selection, data extraction, and risk of bias assessment. Meta-analysis was performed using a multivariate meta-analytic model. Results Twenty-seven cross-sectional studies were included. Multivariate meta-analysis revealed that in tinnitus patients with normal hearing, significantly longer latencies of auditory brainstem response (ABR) waves I (SMD = 0.66 ms, p < 0.001), III (SMD = 0.43 ms p < 0.001), and V (SMD = 0.47 ms, p < 0.01) are present. The results regarding possible changes in middle-latency responses (MLRs) and frequency-following responses (FFRs) were inconclusive. Discussion The discovered changes in short-latency AEPs reflect alterations at brainstem level in tinnitus patients. More specifically, the prolonged ABR latencies could possibly be explained by high frequency sensorineural hearing loss, or other modulating factors such as cochlear synaptopathy or somatosensory tinnitus generators. The question whether middle-latency AEP changes, representing subcortical level of the auditory pathway, are present in tinnitus still remains unanswered. Future studies should identify and correctly deal with confounding factors, such as age, gender and the presence of somatosensory tinnitus components.